2015
DOI: 10.1177/0003319715596281
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Plaques Correlates in Patients With Familial Hypercholesterolemia

Abstract: Patients with familial hypercholesterolemia (FH) are at increased risk of premature cardiovascular disease. We compared factors associated with the presence of carotid plaques and carotid intima-media thickness (cIMT), markers of subclinical atherosclerosis, in 241 patients with FH (98, 40.7% men; mean age 41 ± 18.4 years). Patients with FH having carotid plaques (36.5%) had mean age, apolipoprotein (apo) B, glucose, apoA1, systolic blood pressure (SBP) and diastolic BP, waist/hip ratio (WHR), and body mass in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…4 Various studies have shown an increased incidence and more rapid progression of carotid atherosclerosis in patients with MetS, 6 in both men 7 and women. 8,9 The presence of MetS is associated with an amplified vascular wall thickness and stiffness 10,11 and an overall prothrombotic state. 12 Carotid endarterectomy (CEA) is the current gold standard therapy for carotid artery stenosis caused by atheromatous narrowing at the carotid bifurcation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Various studies have shown an increased incidence and more rapid progression of carotid atherosclerosis in patients with MetS, 6 in both men 7 and women. 8,9 The presence of MetS is associated with an amplified vascular wall thickness and stiffness 10,11 and an overall prothrombotic state. 12 Carotid endarterectomy (CEA) is the current gold standard therapy for carotid artery stenosis caused by atheromatous narrowing at the carotid bifurcation.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown an increased incidence and more rapid progression of carotid atherosclerosis in patients with MetS, in both men and women . The presence of MetS is associated with an amplified vascular wall thickness and stiffness and an overall prothrombotic state …”
Section: Introductionmentioning
confidence: 99%
“…4 Various studies have shown a positive association between MetS and the development of atherosclerosis, resulting in an increased incidence and more rapid progression of carotid atherosclerosis in patients with MetS. [5][6][7] Carotid endarterectomy (CEA) is the preferred treatment for ischemic stroke in selected patients with symptomatic or severe asymptomatic carotid disease. In 2011, a Cochrane analysis showed an absolute risk reduction in ipsilateral ischemic stroke of 16% in patients with a 70% to 99% symptomatic stenosis who underwent CEA compared with best medical treatment alone.…”
Section: Introductionmentioning
confidence: 99%
“…However, their study did not provide information regarding CAD. In addition, similar to prior study, we have found that apoB was associated with the presence of carotid plaques . Unquestionably, more studies about the irrelevant results between Lp(a) and carotid lesions in our observation may be needed considering our small sample size.…”
Section: Discussionmentioning
confidence: 99%